PENGEMBANGAN APLIKASI ANALISIS KINERJA KEUANGAN BERBASIS RASIO UNTUK MENDUKUNG PENGAMBILAN KEPUTUSAN (Studi kasus: Bingkaicanvas.id): (Studi kasus: Bingkaicanvas.id) - Falih, Miftah Zaidan; Nurmiati, Siti (JURNAL REKAYASA INFORMASI, 2024)
In the current digital era, financial performance analysis is a crucial aspect of management decision-making. This research aims to develop a financial ratio-based application that is directly integrated with accounting records to enhance the accuracy and reliability of financial information. The application was developed using observation methods and literature studies, with system design utilizing the Unified Modeling Language (UML). The research findings indicate that the application can facilitate the financial analysis process and support data-driven management decision-making with improved accuracy. Keywords: Financial Report Analysis, Financial Ratios, Financial Performance, Decision Making, UML.